To Assess the Knowledge and Understanding of Importance of Pre-Anaesthesia Assessment in Developing Countries like Pakistan - Anum Sultan, Hamza Bin Ali, Hana Khurshid, Kiran Riaz Khan, Ali Kashif, Samina Ashraf, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the knowledge and understanding of importance of pre-anaesthesia assessment in developing countries like Pakistan. Design: Consecutive non-probability sampling Setting: CMH, Rawalpindi Subjects: All the patients coming to preanaesthesia assessment clinics for preoperative anaesthesia assessment Statistical Analysis: All statistical analysis was done in SPSS Ver. 22.0, descriptive analyses were used in terms of frequency and percentages, and unpaired t test was used to test the significance. Interventions: A predefined questionnaire was filled either passively by the doctor or actively by the patients themselves before being evaluated for anaesthesia fitness Result: About 50.6% of the population knew that they had come to the PAC for PAA and risk assessment, whereas 30.1% and 18.5% said they had come because the surgeon had ordered them to do so or to get the date of the surgery, respectively. 62.7% were aware that anaesthesiologist does the PAA, whereas the rest were not sure. On being asked why PAA is necessary 49.1% replied that it reduces the risks associated with surgery and anaesthesia whereas 29.5% said it helps to get the date of surgery. All these responses were compared with literacy levels and to their history of prior exposure to PACs, all of them were statistically significant with a p value <0.15. Practical Implications: The aim of this study was to know the importance of preanaesthesia assessment among the general population of a developing country like Pakistan coming for surgery, almost half of the patients were unaware of the purpose and were just obeying their surgeons advice to visit PACs, this attitude is what needs to be eliminated and awareness should be created among patients and also surgeons by incorporating importance of anaesthesia related risks in morbid patients and importance of preanaesthesia assessment and investigation Conclusion: Knowledge and perception regarding preanesthesia assessment is still lacking resulting in post-op complications for the patients and there is need of creating awareness regarding PAA so that complications could be avoided. Keywords: preanaesthesia assessment (PAA), preanaesthesia clinics (PACs), questionnaire, third world countries.